2017
DOI: 10.1371/journal.pcbi.1005304
|View full text |Cite
|
Sign up to set email alerts
|

Suboptimal Criterion Learning in Static and Dynamic Environments

Abstract: Humans often make decisions based on uncertain sensory information. Signal detection theory (SDT) describes detection and discrimination decisions as a comparison of stimulus “strength” to a fixed decision criterion. However, recent research suggests that current responses depend on the recent history of stimuli and previous responses, suggesting that the decision criterion is updated trial-by-trial. The mechanisms underpinning criterion setting remain unknown. Here, we examine how observers learn to set a dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 36 publications
5
32
0
Order By: Relevance
“…This has been established for various 6 attributes, from basic features including orientation (Cicchini, Mikellidou, & Burr, 2017;7 Fischer & Whitney, 2014; Fritsche, Mostert, & de Lange, 2017) and numerosity (Cicchini,8 Anobile, & Burr, 2014) to face identity (Liberman, Fischer, & Whitney, 2014). Using 9 categorization tasks, positive serial dependence was found for attributes such as orientation 10 (Cicchini et al 2017;Norton, Fleming, & Daw, 2017), motion (Alais, Leung, & Van der Burg, 11 2017) and gender of face (Taubert, Alais, & Burr, 2016), while a repulsive serial dependence 12 was found for motion-induced orientation (Alais et al, 2017), facial expression (Taubert et al, 13 2016). These studies investigated serial dependence by examining how the previous stimulus 14 influences current perception, but another way to look at serial dependence is to examine how 15 previous responses affect current perceptual decision making.…”
mentioning
confidence: 98%
“…This has been established for various 6 attributes, from basic features including orientation (Cicchini, Mikellidou, & Burr, 2017;7 Fischer & Whitney, 2014; Fritsche, Mostert, & de Lange, 2017) and numerosity (Cicchini,8 Anobile, & Burr, 2014) to face identity (Liberman, Fischer, & Whitney, 2014). Using 9 categorization tasks, positive serial dependence was found for attributes such as orientation 10 (Cicchini et al 2017;Norton, Fleming, & Daw, 2017), motion (Alais, Leung, & Van der Burg, 11 2017) and gender of face (Taubert, Alais, & Burr, 2016), while a repulsive serial dependence 12 was found for motion-induced orientation (Alais et al, 2017), facial expression (Taubert et al, 13 2016). These studies investigated serial dependence by examining how the previous stimulus 14 influences current perception, but another way to look at serial dependence is to examine how 15 previous responses affect current perceptual decision making.…”
mentioning
confidence: 98%
“…First, in categorization tasks, history effects occur as the likelihoods (Norton et al, 2017) implicated in sensory acquisition and discrimination rather than motor control.…”
mentioning
confidence: 99%
“…category A and was clockwise of the criterion line or if the ellipse belonged to category 66 B and was counter-clockwise of the criterion line. The overt-criterion task is an 67 explicit version of the covert-criterion task developed by Norton et al [16]. The 68 overt-criterion task provides a richer dataset than the covert-criterion task in that it 69 affords a continuous measure and allows us to see trial by trial changes in the reported 70 decision criterion, at the expense of being a more cognitive task.…”
mentioning
confidence: 99%
“…Most 464 notably, for all except the RL model we assumed knowledge of the category 465 distributions. However, Norton et al [16] found that for the same 466 orientation-categorization task, category means were estimated dynamically, even after 467…”
mentioning
confidence: 99%
See 1 more Smart Citation